2017
DOI: 10.1634/theoncologist.2016-0357
|View full text |Cite
|
Sign up to set email alerts
|

Dosing Three-Drug Combinations That Include Targeted Anti-Cancer Agents: Analysis of 37,763 Patients

Abstract: These findings serve as a safe starting point for dosing novel three-drug combinations involving a targeted agent in clinical trials and practice. 2017;22:576-584 IMPLICATIONS FOR PRACTICE: Targeted and cytotoxic drug combinations can improve efficacy and overcome resistance. More knowledge of safe starting doses would facilitate use of combinations in clinical trials and practice. Analysis of 37,763 subjects (243 combinations) showed three drugs could be safely administered, but less than 30% of combinations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 34 publications
0
29
0
1
Order By: Relevance
“…However, recent advances in NGS and molecular profiling have demonstrated that each tumor has a unique molecular profile, which mandates a more personalized approach . Recent studies have explored dosing of novel combinations of targeted agents, cytotoxics and immunotherapies . The FDA recently approved pembrolizumab in a tissue‐agnostic manner for use in all patients with MSI‐H status or mismatch gene alterations, which signifies a major shift in drug approval practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent advances in NGS and molecular profiling have demonstrated that each tumor has a unique molecular profile, which mandates a more personalized approach . Recent studies have explored dosing of novel combinations of targeted agents, cytotoxics and immunotherapies . The FDA recently approved pembrolizumab in a tissue‐agnostic manner for use in all patients with MSI‐H status or mismatch gene alterations, which signifies a major shift in drug approval practice.…”
Section: Discussionmentioning
confidence: 99%
“…39,40,43 Recent studies have explored dosing of novel combinations of targeted agents, cytotoxics and immunotherapies. 3,[44][45][46] The FDA recently approved pembrolizumab in a tissue-agnostic manner for use in all patients with MSI-H status or mismatch gene alterations, 47 which signifies a major shift in drug approval practice. Additional studies have suggested that patients with high TMB 12 or PD-L1 expression 14 will have superior responses to checkpoint blockade immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested a possible rationale for dosing combinations with targeted and cytotoxic agents. [10][11][12] Indeed, based on the crucial role that combination treatments are likely to play in improving outcome, more knowledge about the efficacy and safety of combining non-cytotoxic agents for the treatment of advanced solid tumors is needed. We performed a systematic review of randomized trials designed to treat advanced/metastatic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analysis of Phase I clinical trials completed during 2011-2013 showed that on the whole, trials that used molecular biomarker information to influence treatments gave better results than trials that did not (Schwaederle et al 2016). However, most precision oncology treatments utilize only one or two treatments, and resistant clones frequently emerge, emphasizing the need to deliver personalized medicine as multiple treatments combined together (Arnedos et al 2014;Schwaederle et al 2016;Nikanjam et al, 2017;Rebollo et al 2017;Sureda et al 2018;Sicklick et al 2019).…”
Section: Introductionmentioning
confidence: 99%